Pendidikan Ramah Anak dalam Standar Nasional Pendidikan Indonesia: Child Friendly Education in Indonesia's National Education Standards - Amrullah, Muhlasin; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2019)
The aim of this study is to find out child-friendly education within the framework of national education standards. This research is library research whose main sources are library data, all library data are analyzed by data analysis techniques with comparative descrip- tive techniques and critical analysis. Based on the results of educational research in Indonesia, it must at least meet the standards set by the government or known as BNSP badan nasional standar pendidikan or the minimum criteria must be met by educational institutions in conducting education, including 1) Competency Standards for Graduates, 2) Standard Contents 3 ) Process Standards, 4) Education Standards and Education Per- sonnel, 5) Facilities and Infrastructure Standards, 6) Management Standards, 7) Educa- tion Financing Standards, 8) Educational Assessment Standards, out of the eight criteria, education must fulfill the child-friendly elements, according to children's needs, providing affordable access to infrastructure for children, and providing comfort from all threats that threaten children both psychologically and physically.